2010
DOI: 10.5194/nhess-10-857-2010
|View full text |Cite
|
Sign up to set email alerts
|

A reconnaissance study of radon concentrations in Hamadan city, Iran

Abstract: Abstract. This paper presents results of a reconnaissance study that used CR-39 alpha track-etch detectors to measure radon concentrations in dwellings in Hamadan, western Iran, significantly, built on permeable alluvial fan deposits. The indoor radon levels recorded varied from 4 (i.e. below the lower limit of detection for the method) to 364 Bq/m 3 with a mean value of 108 Bq/m 3 which is 2.5 times the average global population-weighted indoor radon concentration -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Fathabadi et al (2006) studied the exposure of miners to radon and its decay products in 12 non-uranium underground mines and indicated that the radon exposure dose is relatively high (10-31 mSv year −1 ) in three mines only. Gilmore and Vasal (2009) conducted a reconnaissance study on radon concentrations in dwellings in Hamadan, western Iran built on permeable alluvial fan deposits. Mowlavi and Binesh (2006) measured radon concentrations in eight springs, deep wells, and river water resource of Mashhad Province, northeastern Iran, and indicated that some samples have radon concentration of more than 10 Bq l −1 .…”
Section: Iranmentioning
confidence: 99%
“…Fathabadi et al (2006) studied the exposure of miners to radon and its decay products in 12 non-uranium underground mines and indicated that the radon exposure dose is relatively high (10-31 mSv year −1 ) in three mines only. Gilmore and Vasal (2009) conducted a reconnaissance study on radon concentrations in dwellings in Hamadan, western Iran built on permeable alluvial fan deposits. Mowlavi and Binesh (2006) measured radon concentrations in eight springs, deep wells, and river water resource of Mashhad Province, northeastern Iran, and indicated that some samples have radon concentration of more than 10 Bq l −1 .…”
Section: Iranmentioning
confidence: 99%
“…The Radosys system is also calibrated by the manufacturer for each new batch of track-etch detectors. The Radosys system was operated then, as described previously, by Gillmore and Jabarivasal (2010). Radon gas forms tracks in the CR39 plastic, with a linear response up to 5000 kBq h m −3 .…”
Section: Methodsmentioning
confidence: 99%
“…Owing to its density, radon is approximately 7.6 times denser than air, it tends to accumulate where ventilation is inadequate. This is considered by Gillmore and Jabarivasal (2010), in a region where there are still limited data on indoor radon concentrations. They undertook a study of radon concentrations in Hamadan City, Iran, using CR-39 SSNTDs.…”
Section: Radon As a Hazard And Hazard Diagnosticmentioning
confidence: 99%